Study Description: Knowledge of Post-Stroke Patient Diet at RSD K.RM.T Wongsonegoro Hospital in Semarang: Bahasa (Journal of Vocational Health Science, 2023)
Background: the stroke is a condition in which an area of the brain's blood vessel is interrupted. This situation may lead to brain cell death and various psychological and physical problems for stroke patients Purpose: this research described the patient dietary pattern knowledge after the stroke in the polyclinic of K.R.M.T Wongsonegoro Hospital, Semarang. Methods: this descriptive quantitative research used a cross-sectional approach. The population consisted of post-stroke patients visiting the polyclinic for further control at K.R.M.T Wongsonegoro hospital, Semarang, from April 15 - 29, 2022. The respondents consisted of 73 respondents. The sampling technique was accidental sampling by applying inclusion and exclusion criteria. The researcher collected the data with Food Frequency Questionnaire. The applied variable was a single variable, the dietary pattern knowledge of the post-stroke patient. Then, the researcher analyzed the data descriptively and statistically. brief summary of study setting and participants; the study design; major methods used to collect and analyze data, including the proper name of instruments used. Results: the results showed most respondents were aged from 56-65 years old, 47.9%. Most respondents were female, 51.1%. Most respondents had excellent dietary pattern knowledge, 76.7%. Conclusion: the results proved that the patients' dietary pattern knowledge after the stroke was excellent. The excellent dietary pattern was observable since most patients knew and understood the importance of keeping the dietary pattern to prevent repeated stroke